Sistem Informasi Dhalang Wayang Kulit: Shadow Puppeteer Information System - iswanto (Global, 2017)
Based on social media information, wayang kulit performances is starting to bloom and is often held in several cities in Java and outside Java, and more new dhalang are emerging from both young and old generations. Every wayang kulit performances always many watched by many people both young and old generation. This shows that the public interest in reverting to traditional culture, especially wayang kulit, has begun to increase. To provide accurate information about dhalang wayang kulit, it is necessary to build an information system that is able to provide information about dhalang which includes contact points, biographies, gagrak, timetable, and collections of audio and video performances. So that observers and puppet fans can get accurate information. This information system can be accessed by the public so that later it can be used as a reference if there will be a staging and also as a reference for conducting other research related to dhalang and shadow puppets.